Wavelength Assignment Techniques with Converters for All Optical Networks (AONs) - Franklin, Paul; Sen, Deboshish (Asian Journal of Engineering and Applied Technology, 2022)
We present an optical routing and wavelength assignment (RWA) technique for the best placement of the wavelength converters. The wavelength converter placement was considered independently at the complete nodes and partial nodes. In comparison to existing approaches, our technique performs better and requires fewer wavelength converters to get the required performance. As much as 7%, the likelihood of blocking is decreased. The study also demonstrates that the top four nodes have the biggest influence over the blocking performance of the network. It is clear that placing the converters in the right location is just as crucial to improving performance as simply adding more converters.